PENGARUH VARIASI JUMLAH SUDU PADA SISTEM PEMBANGKIT LISTRIK TENAGA AIR TERHADAP DAYA YANG DIHASILKAN - Sri Widodo; Kun Suharno; Sigit Mujiarto; Nazarudin Rif’at Rasyidi (Universitas Tidar, 2018)
Indonesia has the potential of water that can become electricity with a hydroelectric power plant. In addition, the distribution of the PLN network has not reached all regions of Indonesia. From these problems the author made a hydropower generator by comparing the number of blades used with a number of 8, 10, and 12 pieces. This study aims to determine the power that will be generated from the number of blades. Data retrieval is done by calculating the power produced by the turbine with a variation of the test time of 20 minutes by 5x. The working principle of this tool is that the water will rotate the wheel connected to the generator with the help of shafts, bearings, pulleys, and V-belts that produce electrical power in the battery so that the electricity can be directly used. The results obtained that the output power is the largest in the use of a number of 12 pieces of blades namely 0.0687 HP, while the number of blades 8 and 10 pieces produces the amount of output power of 0.0627 HP and 0.0652 HP.